Upacara Tabut : Ritual Keagamaan Pada Masyarakat Bengkulu - Ratna Wulan Sari (STIKes Ibnu Sina Ajibarang, 2024)
The Ark ceremony is carried out by the people in Bengkulu city, which is held annually in every month of Muharram, starting on 1-10 Muharram in commemoration of the Shahid of Husen bin Ali bin Abu Talib (grandson of the prophet Muhammad SAW) who died in Padang Kaarbela for defending Islam, which is marked by a coffin called the Ark as a symbol of Husen's body. This ceremony is a cliché because it involves thousands of personalities from the preparation, implementation and organisation stages. This paper aims to reveal the Ark ceremony in the Bengkulu City community by paying attention to all matters related to the implementation of the ceremony, including the background and purpose of the ceremony (history/origin), technical organisers, participants, time, place, equipment and preparations, and the course of the ceremony. The collection of data and information is based on qualitative methods, which is a commonly used approach in cultural research. This research is in the form of explorative-descriptive which seeks to describe and reveal a social reality in people's lives. From the organisation of the Ark ceremony, it is known that the Ark ceremony is a religious ritual that contains local wisdom and cultural values